Wave nonlinear interaction effect on beam-plasma reciprocal influence - Buts, V.A.; Kovpik, O.F.; Kornilov, E.A. (Вопросы атомной науки и техники, 2005)
The authors have examined the oscillation excitation by an extensive nonrelativistic beam of electrons in the beamplasma discharge in the magnetic field when the beam power is about hundreds of kilowatts. It is demonstrated that lowfrequency (LF) ion waves from the range of the low hybrid (LH) resonance play the determinative role in maintaining the beam-plasma discharge. Excitation of such waves is stimulated by the nonlinear interaction between electron plasma oscillation modes of the decay type. The electromagnetic radiation emission from the discharge of pulses is stimulated by the above-mentioned nonlinear interaction, which also causes the wave stochasticity and stabilizes the beam instability. Приведені результати досліджень збудження коливань довгим нерелятивістським електронним пучком при потужності сотні кіловат в пучково-плазмовому розряді в магнітному полі. Показано, що в підтримці пучково- плазмового розряду визначаючу роль відіграють низькочастотні іонні хвилі із області нижчегібридного резонансу. Їх збудження зумовлено нелінійною взаємодією електронних плазмових мод коливань типу розпаду. Електромагнітне випромінювання з розряду імпульсів обумовлене вище вказаною нелінійною взаємодією. Вона і приводить до стохастизації та стабілізації пучкової нестійкості. Проведены результаты исследований возбуждения колебаний протяженным нерелятивистским электронным пучком при мощности сотни киловатт в пучково-плазменном разряде в магнитном поле. Показано, что в поддержании пучково-плазменного разряда определяющую роль играют низкочастотные ионные волны из области нижнегибридного резонанса. Их возбуждение обусловлено нелинейным взаимодействием электронных плазменных мод колебаний типа распада. Электромагнитное излучение из разряда импульсов обусловлено выше указанным нелинейным взаимодействием. Оно же приводит к стохастизации волн и стабилизации пучковой неустойчивости.